2023
DOI: 10.1161/jaha.122.027795
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Atrial Substrate to Predict the Success of Pulmonary Vein Isolation: The Prospective, Multicenter MASH‐AF II (Multipolar Atrial Substrate High Density Mapping in Atrial Fibrillation) Study

Abstract: Background Left atrial substrate may have mechanistic relevance for ablation of atrial fibrillation (AF). We sought to analyze the relationship between low‐voltage zones (LVZs), transition zones, and AF recurrence in patients undergoing pulmonary vein isolation. Methods and Results We conducted a prospective multicenter study on consecutive patients undergoing pulmonary vein isolation‐only approach. LVZs and transition zones (0.5–1 mV) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…Similar patient backgrounds corresponding to types of atrial remodeling have also been reported by Bergonti et al 6 …”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Similar patient backgrounds corresponding to types of atrial remodeling have also been reported by Bergonti et al 6 …”
Section: Discussionsupporting
confidence: 79%
“…LA enlargement has been frequently associated with AF recurrence, 1,2 and is considered one of the most clinically used predictors. The presence and extension of LVAs have also been shown to predict AF recurrence 4–6 . The novelty of this study is that either type of remodeling can develop in populations with different backgrounds, and is associated with AF recurrence.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations